The social cost of CO₂ from the PAGE09 model - Chris W. Hope (Kiel Institute for the World Economy (IfW), 2011)
A new version of the PAGE integrated assessment model, PAGE09, is introduced. The most important scientific, impact, emission and adaptation inputs in the latest default version of the model, PAGE09 v1.7 are described. The scientific and economic impact results are presented for a business as usual (BAU) emissions scenario, and for a low emissions scenario which aims to have a 50% chance of keeping the rise in global mean temperatures below 2 degC. Today's mean social cost of CO2 is about 100 per tonne of CO2 in the BAU scenario, and about 50 per tonne in the low emissions scenario. The major influences on the SCCO2 are found to be the transient climate response, the pure time preference rate, the elasticity of the marginal utility of consumption, the feedback response time of the earth and the weight on non-economic impacts. Less than 10% of the mean SCCO2 comes from impacts in annex 1 from annex 1 emissions, while over 45% comes from impacts in the rest of the world (RoW) from RoW emissions. About one third of the mean SCCO2 comes from impacts in the RoW caused by emissions in annex 1, while just over 10% comes from impacts in annex 1 caused by emissions in the RoW.
Keywords: Q51; Q54; Q58; 330; Climate change; integrated assessment modelling; uncertainty; social cost